2005
DOI: 10.1159/000088382
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Early Diabetic Change with Optical Coherence Tomography in Type 2 Diabetes Mellitus Patients without Retinopathy

Abstract: Purpose: To detect early diabetic damage in type 2 diabetes mellitus patients with no diabetic retinopathy (NDR) using optical coherence tomography (OCT) and to evaluate OCT as a clinical test. Methods: Thirty-two patients with NDR (n = 32) were enrolled. We examined retinal and retinal nerve fiber layer (RNFL) thickness using OCT. Two healthy normal populations were also enrolled for the retinal thickness (n = 48) and RNFL thickness (n = 34). Both OCT measurements were obtained in four areas (temporal, superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
126
3
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 54 publications
18
126
3
5
Order By: Relevance
“…These results are not consistent with the past reports. [12][13][14] One possible reason for this discrepancy may be the shorter duration of the DM in our NDR group than in the other studies, eg, 4.8 ± 4.4 vs 7.9 ± 7.3 years in the data of Sugimoto (Table 5). 14 Abbreviations: NDR, diabetic patients without diabetic retinopathy; OCT, optical coherence tomography; PPDR, preproliferative diabetic retinopathy; RNFL, retinal nerve fibre layer.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…These results are not consistent with the past reports. [12][13][14] One possible reason for this discrepancy may be the shorter duration of the DM in our NDR group than in the other studies, eg, 4.8 ± 4.4 vs 7.9 ± 7.3 years in the data of Sugimoto (Table 5). 14 Abbreviations: NDR, diabetic patients without diabetic retinopathy; OCT, optical coherence tomography; PPDR, preproliferative diabetic retinopathy; RNFL, retinal nerve fibre layer.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, our findings showed that the macular thickness gradually increased with the duration of DM probably because of an increase in vascular permeability in the diabetic retinas. [12][13][14] Because of the short duration of DM, early reduction of macular thickness due to neuronal degeneration was not masked by the increase in macular thickness associated with vascular leakage.…”
Section: Eyementioning
confidence: 99%
See 3 more Smart Citations